Exchange Rate Policy and Trade Balance Problems in Thailand - Wanaset , Apinya (Journal of Applied Economics and Management Strategy, 2023)
The objectives of this study were to study the relationship between exchange rate and international trade balance under Marshall-Lerner condition. The study employed descriptive and quantitative analyses. For quantitative analysis, unit root test and regression analysis were adopted as tools of this study. An analysis was divided into two cases: First, global market is based on annual data from 1990-2019 including world gross domestic product (World GDP), Thai GDP, exchange rate of baht to US dollar, Thai import and export. Second, the trading partners are China, US and Japan, using 86 quarterly data from 1997-2019 including the GDP of Thailand, China, Japan and US together with value of Thai exports to China, Japan and US, value of imports from China, Japan and US, exchange rate of baht to US dollar. The results showed that the relationship between exchange rates and international trade balance, Marshall-Lerner conditions hold in the global market case. That is, sum of the price elasticity of imports and exports is > 1. In the case of trading partners, exchange rate did not significantly affecting on import demand of the three countries. As the products imported from these countries were partly capital goods and some were imported for export. Changes in trade balance depend on other factors than exchange rates. At the same time, it was found that exchange rate affected on Thai exports to the US and Japan except for China. However, considering the conditions Marshall-Lerner, it was found that only a case of Thai-Japanese trade hold under this condition due to the sum of import and export demand-price elasticity > 1. Because the elasticity of Thailand’s export demand to Japan is high, 1.677.